Some New Inequalities for p-Convex Functions via a K-Fractional Conformable Integral - Yan Dou; Muhammad Shoaib Saleem; Nimra Anwar; Haiping Gao (Journal of Mathematics)
The intention of this paper is to develop some new Hermite–Jensen–Mercer type inequalities for p−convex functions via k−fractional conformable integrals. Several existing results are also discussed which can be deduced from our results.